Le droit étatique des minorités religieuses - Zylberberg, Jacques (Les Cahiers de droit, 1986)
For religious minorities, freedoms are best guaranteed by the principle of non-interference, a kind of « right to indifference ». There is no question of denying the existence of oppressed groups, but rather of being opposed to some « class » right for religious groups. The author highlights from the time of Roman history onwards the emancipation and repression of individuals and groups in areas of freedom of conscience and religious practice. He is quite critical towards our era as he underscores the deficiencies in the Canadian and Québec charters in coming to grips with legislative discrimination. According to his conclusions, the non-separation of Church and State and the introduction of statutes on minorities perpetuates discriminated-against minorities.